In defense of the soils. A hybrid perspective of archaeology of agriculture in the Andean high valleys (Catamarca, Argentina) - Taddei Salinas, María Laura (Frontiers in Environmental Archaeology, 2025)
This paper aims at presenting soils as a suitable object for archaeological inquiry and, therefore, as part of material culture. This perspective is based on my Ph.D. research experience developed in three high valleys of north-western Argentina. Soils are the foundation of peasant landscapes, synthesizing a complex interplay of physical, chemical, biological, environmental and social processes. In agriculture, they function simultaneously as both a support and a provider for plant life and, in turn, contributes to a complex assemblage that transforms them into a locus of fertility, nurturing a caregiving environment. Therefore, I suggest conceptualizing this assemblage as the Soil-Earth-Territory Complex, emphasizing both its material and social dimensions. This conceptualization prompts the development of an Archaeology of Soils, which considers their temporal and spatial depth, the multiple vital materials that constitute them, and their dynamic relationship with the processes occurring in, on, and through them. To address such complexity, Hybrid Archaeologies emerge as the most suitable approach, as they allow understanding the central role of the Soil-Earth-Territory Complex in shaping peasant agricultural landscapes within a past-present continuum.